Reproductive seasonality in African ungulates in relation to rainfall - Ogutu, Joseph O.; Piepho, Hans-Peter; Dublin, Holly T. (Commonwealth Scientific and Industrial Research Organisation, 2014)
Context: Reproductive seasonality in ungulates has important fitness consequences but its relationship to resource seasonality is not yet fully understood, especially for ungulates inhabiting equatorial environments.